Gastroesophageal reflux in laryngopharyngeal reflux patients: Clinical features and therapeutic response. (26th December 2019) - Lechien, Jerome R.; Bobin, Francois; Muls, Vinciane; Eisendrath, Pierre; Horoi, Mihaela; Thill, Marie‐Paule; Dequanter, Didier; Durdurez, Jean‐Pierre; Rodriguez, Alexandra; Saussez, Sven
Abstract : Objective: To investigate the clinical features and the therapeutic response of laryngopharyngeal reflux (LPR) patients with or without gastroesophageal reflux disease (GERD). Methods: Patients with LPR symptoms were enrolled from three European Hospitals. The diagnosis of LPR and GERD was made through impedance‐pH monitoring (MII‐pH). A gastrointestinal endoscopy was realized in patients with digestive complaints or ≥60 years old. The 3‐ to 6‐month treatment was based on the association of diet, pantoprazole, alginate, and magaldrate regarding the MII‐pH characteristics. Reflux Symptom Score (RSS) and Reflux Sign Assessment (RSA) were used to evaluate the clinical evolution throughout treatment. The gastrointestinal endoscopy findings, clinical features, and therapeutic response were compared between patients with LPR and GERD (LPR/GERD) and patients with LPR. Results: One hundred and eleven LPR patients were included, 54 being LPR/GERD. LPR/GERD patients had a higher number of proximal reflux episodes compared with LPR patients. The prevalence of esophagitis, hernia hiatal, and lower esophageal sphincter insufficiency did not differ between groups. The presence of GERD was strongly associated with acid LPR. Patients without GERD had a higher proportion of nonacid and mixed LPR compared with LPR/GERD patients. The pre‐ to posttreatment evolutions of RSS and RSA were quite similar in both groups, with the exception of the 3‐ to 6‐month improvement of digestive symptoms, which was better in LPR/GERD group. The therapeutic success rates were 79.6% and 77.2% in GERD/LPR and LPR group, respectively. Conclusion: GERD is predictive of acid LPR. The clinical evolution and the therapeutic response rates were quite similar in both groups. Level of Evidence: 4 Laryngoscope, 130: E479–E489, 2020